Wharton's jelly‐derived stromal cells and their cell therapy applications in allogeneic haematopoietic stem cell transplantation. Issue 5 (28th January 2022) - Pochon, Cécile; Notarantonio, Anne‐Béatrice; Laroye, Caroline; Reppel, Loic; Bensoussan, Danièle; Bertrand, Allan; Rubio, Marie‐Thérèse; D'Aveni, Maud
Abstract: For decades, mesenchymal stromal cells (MSCs) have been of great interest in the fields of regenerative medicine, tissue engineering and immunomodulation. Their tremendous potential makes it desirable to cryopreserve and bank MSCs to increase their accessibility and availability. Postnatally derived MSCs seem to be of particular interest because they are harvested after delivery without ethical controversy, they have the capacity to expand at a higher rate than adult‐derived MSCs, in which expansion decreases with ageing, and they have demonstrated immunological and haematological supportive properties similar to those of adult‐derived MSCs. In this review, we focus on MSCs obtained from Wharton's jelly (the mucous connective tissue of the umbilical cord between the amniotic epithelium and the umbilical vessels). Wharton's jelly MSCs (WJ‐MSCs) are a good candidate for cellular therapy in haematology, with accumulating data supporting their potential to sustain haematopoietic stem cell engraftment and to modulate alloreactivity such as Graft Versus Host Disease (GVHD). We first present an overview of their in‐vitro properties and the results of preclinical murine models confirming the suitability of WJ‐MSCs for cellular therapy in haematology. Next, we focus on clinical trials and discuss tolerance, efficacy and infusion protocols reported in haematology for GVHD and engraftment.